FREE EDUCATION POLICY IN INDONESIA: IMPLEMENTATION CHALLENGES AND THE FULFILLMENT OF CITIZENS' CONSTITUTIONAL RIGHTS: Kebijakan Pendidikan Gratis di Indonesia: Tantangan Implementasi dan Pemenuhan Hak Konstitusional Warga Negara - Nita Cicilia Ganap (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the implementation of free education policy in Indonesia from a constitutional law perspective, aiming to assess the extent to which this public policy aligns with the constitutional mandate under Article 31 of the 1945 Constitution. The research adopts a normative juridical approach combined with empirical analysis to evaluate how free education policies are formulated, implemented, and enforced across different regions. Legal documents, regulations, and policy instruments such as the School Operational Assistance (BOS) program and regional regulations were analyzed alongside field data collected through interviews and case studies. Findings reveal a significant gap between constitutional norms and policy practices, as many schools continue to impose informal fees under various forms—contrary to the constitutional guarantee of free and accessible education. Inconsistent interpretations of regulations at the local level, weak institutional capacity, and inadequate oversight mechanisms contribute to persistent violations. The discussion highlights the need for clearer regulatory formulations, stronger enforcement frameworks, and increased legal awareness among citizens and educational stakeholders. Furthermore, the study underscores the importance of civil society participation and effective governance in ensuring transparency and accountability. Based on these findings, the research recommends harmonizing national and regional regulations, strengthening institutional capacity within schools and local governments, and introducing legal mechanisms such as class action suits to enable citizens to claim their constitutional right to free education. Ultimately, realizing the constitutional promise of free education requires a multidimensional and legally grounded approach that prioritizes justice, equality, and public accountability.